2008
DOI: 10.1111/j.1834-7819.2007.00011.x
|View full text |Cite
|
Sign up to set email alerts
|

Working practices and job satisfaction of Victorian dental hygienists

Abstract: Background:  Increasing demand for dental services and a projected shortage in the oral health workforce in Victoria has focused attention on dental hygienists as one mechanism for increasing the supply of dental services. Understanding the dental hygienist workforce is essential in order to plan effectively for the future delivery of dental services in Victoria.Methods:  A postal survey of a random sample of Victorian dental hygienists was undertaken in 2006. Data on hygienists’ demographic characteristics, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 11 publications
6
17
0
Order By: Relevance
“…This finding is in contrast to which (5) where there is no problem between males and females in searching for a job as a dental hygienist. These findings are closely similar to those results reported by Victorian dental hygienists where employment conditions and salary level were ranked in their satisfaction scale (14). These results are similar to previous studies (8,14), in which dental hygienists were generally satisfied with their location of practice and working hours.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This finding is in contrast to which (5) where there is no problem between males and females in searching for a job as a dental hygienist. These findings are closely similar to those results reported by Victorian dental hygienists where employment conditions and salary level were ranked in their satisfaction scale (14). These results are similar to previous studies (8,14), in which dental hygienists were generally satisfied with their location of practice and working hours.…”
Section: Discussionsupporting
confidence: 91%
“…The findings showed that the most of Jordanian dental hygienists generally satisfied with location of work and flexibility in working hours. These results are similar to previous studies (8,14), in which dental hygienists were generally satisfied with their location of practice and working hours.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations